PERBEDAAN PERBEDAAN POLA ASUH ORANG TUA DENGAN PENGGUNAAN GADGET PADA ANAK DI TK KRISTEN ATAMBUA NTT DAN TK AN-NUR MANCAR PETERONGAN JOMBANG - Sylvie Puspita; Najah Soraya Nia (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2020)
The development of technology is growing rapidly in accordance with the times. Gadgets in early childhood (4-6 years) are not recommended because they can interfere with the natural growth and development process (Hana, 2017). The method used in this study is a cross-sectional retrospective approach. The population in this study were 120 preschool children in Atambua Christian Kindergarten and Islamic Kindergarten in the Jombang area. The side used purposive. The number of samples in this study were 60 kindergarten children consisting of 30 Kindergarten Christians Atmabua and 30 TK An-Nur Jombang. The measuring instrument used in this study was a questionnaire on parenting styles and a questionnaire on the use of gadgets. There are differences in the use of gadets between TK Kristen Atambua and Tk-Anur Jombang. This is evidenced by the results of the Wilcoxon sig-2 tailed 0.013 <0.05. Meanwhile, there is no difference in parenting style, as evidenced by the Wilcoxon sig-2 tailed test value of 0.08> 0.05. Parents are expected to pay more attention to the positive and negative impacts before giving gadgets to pre-school age children. Parenting style, use of gadgets, parents